Prospects For the Development of Innovative Technologies in The Field of Banking Services - Ji Lei; Tatiana Ushkats (Communications of International Proceedings, 2022)
The COVID-19 pandemic and the global economic crisis accelerated digitalization in banks around the world and made adjustments to the life of all mankind, influencing the work, life and lifestyle of people. Banks have to learn to live in a new reality, change their habits and acquire new ones. The main way to combat the spread of the virus is to restrict the movement of people and for some time refuse to attend events, public places, and switch to a remote mode of work. At this time, services that a person can receive remotely become especially relevant. Remote banking systems are all those bank services that allow the client to resolve financial issues without visiting the office, such as mobile applications and Internet banking. In terms of digitalization, Chinese banks have approached the COVID-19 crisis in much better shape than their many international competitors. Rapid digitalization of business processes has helped lending institutions in China ensure that most of their day-to-day operations are done remotely in just a few years, he said. This also allowed China to become a world leader in the development of cashless payments. For commercial banks, the introduction of innovative technologies is a rather complicated and costly process. It includes the involvement of all participants in the banking process. In the context of globalization, innovative technologies in the banking sector are an integral requirement for the activities of commercial banks and an important factor in the choice of their clients. The lack of data implemented by innovative technologies has a negative impact on the bank, which is expressed in a decrease in the number of customers, a decrease in income and profits from the implementation of core activities and, as a result, a decrease in the financial stability and solvency of a financial institution. Researchers have found that people under 25 are more likely to use remote banking products. About 67% of survey participants have a virtual card. Young people also prefer calls and online communication with the bank to visits to branches. 91% of Chinese people use online banking services: 81% of them choose the mobile application, and 54% choose the web version. Overall, 74% of Chinese people who use the internet have bank apps. In mobile services, users most often transfer money (76%), pay for services (65%) and control their expenses (48%) [8]. The scientific novelty of the article lies in the search for methods to improve the remote banking system using the introduction of remote service for the customers of China Minsheng Bank and in assessing the advantages and effectiveness of the Bank with the introduction of this system.
Keywords: commercial bank; remote banking; pandemic; remote banking services; innovation; digitalization.